"Money's too tight (to mention)": a review and psychological synthesis of living wage research. Issue 3 (4th May 2021) - Searle, Rosalind H.; McWha-Hermann, Ishbel
ABSTRACT: Traditional living wage research has been the purview of economists, but recently contributions from the field of work psychology have challenged existing perspectives, providing a different lens through which to consider this issue. By means of a narrative interdisciplinary review of 115 peer-reviewed journal articles published between 2000 and 2020, we chart the transitions in the field with attention shifting from macro-economic and econometric lens largely concerned with the costs of living wage policies, to a more person-centric lens focusing on the employee and their family. Synthesizing prior study, we outline five key themes: consequences for individuals, organizations, and societies; changes in operationalization; exploration of different contexts; study of social movements; and the history of the topic. We outline the importance of work psychology in developing the living wage debate through more inclusive definitions, and novel operationalization and measurement, thereby providing fresh insights into how and why living wages can have a positive impact. Critically, we outline the redundancy of simple study of wage rates without understanding the elements that make work decent. We raise key areas for further study, and this topic presents a significant opportunity for psychology to shift focus to impact upstream policy by providing new empirical evidence, and challenges to structural inequalities.